Preparation of ZSM5 from Several Types of Coal Fly Ash using Hydrothermal Method for Catalytic Pyrolysis using Heat Pipe as a Passive Cooling for High-Density Polyethylene Waste - Desy Kurniawati, Nandy Putra, Nasruddin Abdullah, Agus Nurrokhmat (International Journal of Advanced Science and Technology, 2020)
Plastic waste processing technology is advancing to minimize the growing plastic wastetoday. HDPE (high-density polyethylene), one type of plastic that is widely used in ourdaily lives, representing plastic waste that takes a long time to unravel naturally. Thisstudy discusses the preparation of the ZSM5 catalyst as the main component, which ismade from several types of Indonesian coal fly ash. It will be used to convert HDPE wasteinto diesel fuel using low energy pyrolysis technology with liquid collection system. Thepyrolysis process used is a thermal pyrolysis with a passive cooling system, consisting ofseveral straight heat pipes, which are run for the raw material 50g on the temperatureprocess done at 500 and 550 °C in 3 hours. Therefore, ZSM5 as a catalyst is necessary toaid the process of converting plastic waste to diesel fuel, which is expected to have thesame characteristics as diesel by developing thermal pyrolysis for catalytic pyrolysis.ZSM5 as catalysts are also made from the power plants’ fly ash of the four different typesof coal, namely Amurang, Bukit Asam, Adaro and Kidenco. Furthermore, the best type offly ash is selected to create ZSM5. The minimum Si/Al ratio is 5, ideally in the range of 5-50. The ratio value of the fly ashes of Amurang, Bukit Asam, Adaro, and Kidenco are21.95,10.02, 2.40, and 3.79, respectively. Thus, Amurang and Bukit Asam fly ashes wereselected to be formed into ZSM5. In the next step, Amurang and Bukit Asam fly ashes areprocessed by hydrothermal methods to remove impurities by using 10 M HCl which isheated at 550oC for 1 hour to obtain Supernatan solution, then added sodium dodecylsulfate (SDS) 0.21 M and NH4OH until reaches PH of 9.5-10. The fly ash is then heatedin the oven at a temperature of 97 oC for 5 days, and then heated again for 5 days in anoven with a temperature of 550 oC. BET (Brunaeur-Emmet-teller) test as a testcharacteristic catalyst is performed on the results ZSM5. The results of ZSM5 BET testshowing the surface area of Amurang fly ash (9.11 m2/g); Bukit Asam fly ash (21.25m2/g), volume of pore Amurang fly ash (0.02 ml/g); Bukit Asam fly ash (0.03 ml/g), andthe pore size Amurang fly ash (40.12 Å); Bukit Asam fly ash (25.93 Å). From these resultsit can be stated that the pore size matches the characteristics of ZSM5.